Genotypic Distribution and the Epidemiology of Multidrug Resistant Tuberculosis in Upper Northern Thailand - Sukanya Saikaew; Aksara Thongprachum; Rodjana Pongsararuk; Aungkana Thanraka; Naowarat Kunyanone; Boonchai Chaiyasirinroje; Praphan Luangsook; Bordin Butr-Indr; Ponrut Phunpae; Usanee Wattananandkul (MDPI AG, 2022)
The epidemiology and genotypes of multidrug-resistant tuberculosis (MDR-TB), a global public health threat, remain limited. The genotypic distribution and factors associated with MDR-TB in upper northern Thailand between 2015 and 2019 were investigated. The DNA sequencing of rpoB, katG, and inhA promoter of 51 multidrug-resistant Mycobacterium tuberculosis isolates revealed nine patterns of the rpoB gene mutation distributed in seven provinces. The S531L mutation was the most common mutation in all provinces. The rpoB mutation in Chiang Rai, Chiang Mai, and Lampang was highly diverse compared to other areas. Here, the mutation profiles that have yet to be reported in northern Thailand (H526P, Q513P, and H526C) were detected in Chiang Rai province. The S315T katG mutation was the most common genotype associated with INH resistance, especially in Chiang Mai and Lampang. Further analysis of data from 110 TB patients (42 MDR-TB and 68 drug-susceptible TB) revealed that <60 years of age was a significant factor associated with MDR-TB (OR = 0.316, 95% CI 0.128-0.784, p = 0.011) and ≥60 years of age was a significant factor associated with the S315T katG-mutation (OR = 8.867, 95% CI 0.981-80.177, p = 0.047). This study highlighted the necessity for continuous surveillance and risk factor monitoring for effective control of MDR-TB.